Heterotic twistor-string theory - Mason, L; Skinner, D (2008)
We reformulate twistor-string theory as a heterotic string based on a twisted (0, 2) model. The path integral localizes on holomorphic maps, while the (0, 2) moduli naturally correspond to the states of N = 4 super-Yang-Mills and conformal supergravity under the Penrose transform. We show how the standard twistor-string formulae of scattering amplitudes as integrals over the space of curves in supertwistor space may be obtained from our model. The corresponding string field theory gives rise to a twistor action for N = 4 conformal supergravity coupled to super-Yang-Mills. The model helps to explain how the twistor-strings of Witten and Berkovits are related and clarifies various aspects of each of these models. © 2007 Elsevier B.V. All rights reserved.